Draft genome sequence of Pasteurella multocida subsp. multocida strain PMTB, isolated from a buffalo - Yap, Huan Yong; Ghazali, Kamal; Wan Mohamad Nazarie, Wan Fahmi; Mat Isa, Mohd Noor; Zakaria, Zunita; Omar, Abdul Rahman (American Society for Microbiology, 2013)
Pasteurella multocida serotypes B:2 and E:2 are the main causative agents of ruminant hemorrhagic septicemia in Asia and Africa, respectively. Pasteurella multocida strain PMTB was isolated from a buffalo with hemorrhagic septicemia and has been determined to be serotype B:2. Here we report the draft genome sequence of strain PMTB.